Bianchi type- I, III, V, VIo and Kantowski-Sachs models in scalar-tensor theories with dynamic cosmological constant - Singh T.; Chaubey R. (My University, 2025)
The effect of a time-dependent cosmological constant is considered in a family of scalar-tensor theories. The Bianchi type I, III, V, VIo and Kantowski-Sachs models for vacuum and perfect fluid matter are found. The gravitational constant decreases with time so that these models satisfy the Dirac hypothesis. The "cosmological constant" also decreases with time, therefore it can have a very small value at the present time. © 2008 Springer Science+Business Media B.V.